Kontribusi Ilmu Sosiologi Terhadap Pendidikan Dan Pembentukan Kepribadian Anak - Sani Shara Pratita Andani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2026)
Sociology plays a crucial role in understanding the changes occurring in education and the development of children's character. By adopting sociological methods, education is seen as more than just a process of imparting knowledge; it also serves as a means to instill values, norms, and culture in society. This study aims to investigate the contribution of sociology to education, particularly in terms of children's character development. In this study, the method applied is library research, which includes analysis of various books, journals, and previous research. The results show that sociology makes a significant contribution to understanding social interactions in schools, relationships between students and teachers, family influences, and how society shapes children's character. This discussion emphasizes that education functions as a primary socialization agent that connects children to the social world. Ultimately, sociology acts as a theoretical and practical foundation in developing education that focuses not only on cognitive aspects but also pays attention to the emotional side and the formation of children's character as a whole.